Zu, ou les possibles d’une pensée japonaise du design - Nolwenn Maudet (Appareil)
Design theories developed outside of English are almost invisible in France. Building on an example of a Japanese design theory, we explore some of the possibilities and limits of developing design theories outside of English. This text, written in 1981 by designer and educator Tadanori Nagasawa, introduces the notion of zu 図, an untranslatable Japanese term that “covers almost all forms of two dimensional graphic representation, other than pictorial images and straight prose”. After a first reflexive translation and acculturation of this notion that allows us remove the partitions between design disciplines by focusing on its common tools, we question the possibility of a non-anglo-centric theory of design. Nagasawa’s theory, while based on a Japanese notion, is still a bilingual theory, developed under the scrutiny of English in a text written for anglophone readers. A second analysis of Nagasawa’s text reveals how his theory of zu builds on some of the specificities of the written Japanese language system and questions some of the potentialities of this language as a framework for thinking about design.